In vitro evaluation of the antibacterial effects of monomer components of Pithecellobium clypearia against aquatic pathogens and synergy with enrofloxacin - Wenhao Wu; Jiahao Zhang; Xiaoyin He; Wei Li; Chun Liu; Biao Jiang; Youlu Su (Aquaculture Reports)
Traditional Chinese medicine (TCM), renowned for environmentally friendly and natural characteristics, has emerged as a promising alternative to conventional antibiotics. This study evaluated the antibacterial efficacy of six TCM-derived monomers (quercetin, luteolin, pyrogallol, gallic acid, tannic acid, and L-epicatechin) from Pithecellobium clypearia against 11 stains of aquatic pathogens, including a drug-resistant Aeromonas schubertii strains. Employing the Oxford cup diffusion and micro broth dilution methods, we discovered these components demonstrated varying degrees of antibacterial activity against the tested pathogens. Pyrogallol, luteolin and tannic acid exhibiting particularly remarkable performance. with pyrogallol exhibiting an impressive minimum inhibitory concentration (MIC) of just 15.63 µg/mL, and luteolin and tannic acid ranged from 62.50 to 500 µg/mL. These compounds demonstrate greater efficacy against the multi-drug resistant Aeromonas schubertii strain WL23R compared to the sensitive A. schubertii strain WL23S, indicating their potential in combating antibiotic resistance. Additionally, the combination of pyrogallol, luteolin, and tannic synergy with enrofloxacin (ENR) enhanced the potency of existing antimicrobials and potentially reducing dosage needs. These results provided evidence that the six monomers, particularly pyrogallol, luteolin, and tannic acid, exhibited substantial antibacterial properties with potential applications as antibiotic alternatives in aquaculture.